2023
DOI: 10.1117/1.ap.5.1.016003
|View full text |Cite
|
Sign up to set email alerts
|

Massively parallel universal linear transformations using a wavelength-multiplexed diffractive optical network

Abstract: Large-scale linear operations are the cornerstone for performing complex computational tasks. Using optical computing to perform linear transformations offers potential advantages in terms of speed, parallelism, and scalability. Previously, the design of successive spatially engineered diffractive surfaces forming an optical network was demonstrated to perform statistical inference and compute an arbitrary complex-valued linear transformation using narrowband illumination. We report deep-learning-based design … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 73 publications
2
33
0
Order By: Relevance
“…Furthermore, some of the emerging digital imaging techniques that are optimized to see through random scattering media are unlikely to compromise our data‐class encryption scheme enabled by diffractive networks due to their requirement of prior knowledge of the scattering medium properties [ 38–41 ] or the input‐output measurement pairs. [ 42–45 ] In addition to these, due to the absorbing/blocking areas of a D 2 NN, its architecture does not present time‐reversal symmetry; [ 21 ] when this feature is combined with the fact that the optical phase information is lost at the image sensor‐array, it becomes unattainable for adversaries to decipher the original input objects through backward field propagation operations applied on the acquired intensity‐only images, further reinforcing our system's security.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, some of the emerging digital imaging techniques that are optimized to see through random scattering media are unlikely to compromise our data‐class encryption scheme enabled by diffractive networks due to their requirement of prior knowledge of the scattering medium properties [ 38–41 ] or the input‐output measurement pairs. [ 42–45 ] In addition to these, due to the absorbing/blocking areas of a D 2 NN, its architecture does not present time‐reversal symmetry; [ 21 ] when this feature is combined with the fact that the optical phase information is lost at the image sensor‐array, it becomes unattainable for adversaries to decipher the original input objects through backward field propagation operations applied on the acquired intensity‐only images, further reinforcing our system's security.…”
Section: Discussionmentioning
confidence: 99%
“…Diffractive feature size and layer-to-layer separation were set such that this diffractive processor works with a numerical aperture (NA) of ≈1 and has adequate degrees of freedom to approximate the designed transformation tasks with high fidelity. [15,30,37] The number of diffractive layers used in our designs was empirically determined based on the task complexity, practical/experimental challenges, and diminishing performance improvement associated with additional layers. Numerical simulations showed that the performance of a D 2 NN improves with an increased number of diffractive layers due to the additional degrees of freedom that grant higher design flexibility and better approximation accuracy, by avoiding the power dominance of ballistic photons that diffract within a low NA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further enhance the unidirectional imaging performance of these diffractive designs, one strategy would be to create deeper architectures with more diffractive layers, also increasing the total number ( N ) of trainable features. In general, deeper diffractive architectures present advantages in terms of their learning speed, output power efficiency, transformation accuracy, and spectral multiplexing capability ( 39 , 44 , 47 , 48 ). Suppose an increase in the space-bandwidth product (SBP) of the input FOV A (SBP A ) and the output FOV B (SBP B ) of the unidirectional imager is desired, for example, due to a larger input FOV and/or an improved resolution demand; in that case, this will necessitate an increase in N proportional to SBP A × SBP B , demanding larger degrees of freedom in the diffractive unidirectional imager to maintain the asymmetric optical mode processing over a larger number of input and output pixels.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we introduce the design of a snapshot multispectral imager that is based on a diffractive optical network (also known as D 2 NN, diffractive deep neural network [51][52][53][54][55][56][57][58][59][60] ) and demonstrate its performance with 4 (2 × 2), 9 (3 × 3) and 16 (4 × 4) unique spectral bands that are periodically repeating at the output image FOV to form a virtual multispectral filter array. This diffractive network-based multispectral imager (Fig.…”
Section: Introductionmentioning
confidence: 99%